Investigations of the mechanism of the fouling in microgranular adsorptive filtration - Malczewska Beata (Journal of Water and Land Development, 2017)
The application of microgranular adsorptive filtration (μGAF) has been successfully used in conjunction with membrane filtration. It proves to be efficient not only in removal of natural organic matter (NOM) but also it significantly reduces the extent of fouling. There are a few mathematical models evaluated to understand the underlying mechanism of fouling. This paper describes a method of predicting filtration capacities using constant flow datasets collected when μGAF was applied. The results suggest that the behaviour of fouling in microgranular adsorptive filtration system varies between different filtration operations and natural water quality. In analysed case the mechanism of pores blocking can be described by the complete blocking mechanism.